Increasing Students’ Motivation and Geography Learning Outcomes Through Pq4r Strategy Based on Crossword Puzzle - Rahman, Suhadi; Erianjoni, Erianjoni; U, Iswandi; Anwar, Syafri (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
Education is a long life need. Every human being needs education, when and wherever he is. Education is very important because without human education it will be difficult to develop and even be retarded. Education is a conscious endeavor and aims to develop quality. The definition of education according to the Law (UU) of the National Education System No. 20/2003 is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious-spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation, and state. With education, it is hoped that humans will know all the advantages that have the potential for a better quality of life than before. Based on the findings obtained, it can be concluded that learning outcomes are the abilities possessed by students after receiving their learning experiences and these results can be used by teachers to be used as measures or criteria in achieving an educational goal and this can be achieved if students understand learning with accompanying learning by changing behavior for the better.